Trainer Kit Module for DC Motor Speed Control Using Voice Commands Based on Arduino - Khalid, Muhammad; Fathiah, Fathiah; Gufran , Gufran Ibnu Yasa (Department of Electrical Engineering Education, Faculty of Engineering, State University of Manado, 2024)
Based on the results of observations made by researchers through direct observation of lecturers in the field of electricity Electrical Engineering Education Study Program it was found that there is a need for additional trainers as learning media in the electrical machine control course This study aims to find out how to design a trainer kit design module for DC motor speed control using voice commands by utilizing the Arduino microcontroller We also learned the results of testing the design of a trainer kit design module for DC motor speed control using voice commands by utilizing the Arduino microcontroller The research method researchers use is the Research and Development R amp;D method which aims to develop new products or innovations that benefit Based on the results of expert validation it can be concluded that the Arduino Microcontroller Based Trainer Kit Practical Module obtained a high percentage of media experts at 96 material experts at 95 5 and language experts at 80 These results indicate that this module gets the Very Eligible category to be applied to the Electrical Machine Control course < p>